Review of Heterostigmatic species (Acari: Prostigmata) in Turkey with four new records - Cobanoglu, Sultan; Erdogan, Tugba; Cilbircioglu, Cihan (Systematic and Applied Acarology Society, 2021)
This paper reviews the Heterostigmata (Acari: Prostigmata) in Turkey, with an updated checklist of 41 species belonging to 7 families and 16 genera. Heterostigmatic mites Kerdabania variabilis Khaustov (Neopygmephoridae), Tarsonemus talpae Schaarschmidt (Tarsonemidae); T. bilobatus Suski and T. aequalis Livshits, Mitrofanov & Sharonov were identified as new records for mite fauna of Turkey. Tarsonemus smithi Ewing and T. waitei Banks have also been found during this study. The samples were collected during the vegetation periods from garlic growing areas and fruit orchards in Kastamonu and Ankara, Turkey, during the period 2012–2015. The plant samples were extracted by using Berlese funnel and the specimens were mounted in micro slides in Hoyer’s medium. Collection data and geographical distribution of these species are provided. Besides, Heterostigmata species which were previously reported from Turkey are also presented here.